Pengembangan Model Diskusi Berbasis Whatsapp Untuk Meningkatkan Pemahaman Konsep Pada Mata Kuliah Fisika Statistik - Aminoto, Tugiyo; Dani, Rahma (EduFisika: Jurnal Pendidikan Fisika, 2018)
The limited time and low participation of students in discussion activities in the classroom causes the optimal process of lecturing, especially in the subjects of statistical physics. On the other hand, the rapid development of information technology and social media and the occurrence of a paradigm shift in learning to be an active creative education bring challenges and solutions. The number of lecturers and students who use social media Whatsapp, media that allows sharing of information online, easy, fast and cheap, is an alternative solution for the not optimal learning process in the classroom so far. So it is necessary to do research that produces a social media-based technology integration model for discussion activities outside the classroom. This type of research takes the form of research and development. The process of developing learning media with online discussion using whatsapp refers to the Four-D development model which includes 4 stages: Define, design, development, and Dissemination. The results generated are whatsapp-based online discussion models that can be used as a reference for educators who will utilize whatsapp social media in learning both in school and college. Keywords: information technology, Whatsapp, online discussion, integration model